2000
DOI: 10.1159/000028983
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the Hypophysis

Abstract: The authors describe an 11-year-old girl with duplication of a pituitary gland and hypertelorism. Of the 14 cases described to date, only 2 others have lacked associated major facial or oral anomalies. Two separate glands, respective stalks and hypothalamic enlargement were incidentally found on MR imaging performed to evaluate the patient’s complaint of anosmia. A tortuous fusiform dilatation of one pericallosal artery was also discovered. A review of hypophyseal embryogenesis is presented. It is now evident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…Like us, some authors also found a segmental dilatation of the distal anterior cerebral artery, i.e. the pericallosal vessel [7], but we also noticed a dilatation of the extradural segment of both vertebral arteries (Fig. 2).…”
Section: Double Pituitary Glandsupporting
confidence: 86%
See 4 more Smart Citations
“…Like us, some authors also found a segmental dilatation of the distal anterior cerebral artery, i.e. the pericallosal vessel [7], but we also noticed a dilatation of the extradural segment of both vertebral arteries (Fig. 2).…”
Section: Double Pituitary Glandsupporting
confidence: 86%
“…duplication, of the basilar artery, as was noticed in some other patients [7,23,44,49]. The latter anomaly seems to be a characteristic features in patients with the pituitary duplication [44].…”
Section: Double Pituitary Glandmentioning
confidence: 74%
See 3 more Smart Citations